The correlation between untreated caries and the nutritional status of 6–12 years old children in the Medan Maimun and Medan Marelan sub-district - Siti Salmiah; L. Luthfiani; Zulfi Amalia; Deandini Kusumah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: In Indonesia, dental caries constitute one of the most common dental health problems in children. Untreated dental caries will cause both pain and inconvenience when eating, resulting in a reduced appetite which can negatively affect the Body Mass Index (BMI). Purpose: This study aimed to investigate the correlation between untreated caries and nutritional status in children aged 6-12 years old in the Medan Maimun and Medan Marelan sub-districts. Methods: An analytical observation study with cross-sectional design was adopted. The number of child subjects totaled 350, divided into two groups, namely; the PUFA/pufa group (n=172) and the Non-PUFA/pufa group (n=178). Samples were selected on the basis of purposive sampling. Oral examination was subsequently performed using the PUFA/pufa index. The height and weight of the subjects were assessed according to the Indonesian Ministry of Health’s BMI criteria of 2011. Thereafter, Chi square, Spearman and Mann-Whitney tests were all performed as analytical tests. Results: The results of this research revealed a significant correlation between caries status and BMI (p<0.001) in both the PUFA/pufa and Non PUFA/pufa groups (r=-0.515), as well as between the mean PUFA/pufa score and age. However, there was no significant correlation between the mean PUFA/pufa score and gender. Conclusion: It can be concluded that a correlation exists between untreated caries and the nutritional condition of children aged 6-12 years old in the Medan Maimun and Medan Marelan sub-districts.